Participamos en la elaboración de nuestras normas de convivencia - Medina Saldaña, Karin Elizabeth (2019)
The present work is focused basically on improving the relations of coexistence. It primarily deals with the rules of coexistence: a set of rules or social norms that is as important to inculcate the children as to teach them the alphabet or to eat with cutlery. These norms enable us to live together in peace and harmony, avoiding discord. The norms, values, forms and behavior of a child such as greeting on arrival, saying goodbye when leaving, giving thanks or asking for forgiveness - very simple rules of courtesy - can be acquired by children from an early age. However, they are not the only norms or rules of coexistence. The learning session "We participate in the development of our rules of coexistence" is designed for students of the first grade of primary education of the Educational Institution "Abraham Valdelomar No. 80005" - Trujillo. It aims to develop the students’ ability to express their interests, feelings and emotions in various everyday situations within the classroom according to the roles they fulfill in it. In the elaboration of this session, didactic processes of the area of Social Personnel were used. Strategies designed to promote the active and meaningful participation of all students were applied. As an assessment tool, a checklist was employed.